2020
DOI: 10.1098/rspa.2020.0671
|View full text |Cite
|
Sign up to set email alerts
|

Three-phase flow displacement dynamics and Haines jumps in a hydrophobic porous medium

Abstract: We use synchrotron X-ray micro-tomography to investigate the displacement dynamics during three-phase—oil, water and gas—flow in a hydrophobic porous medium. We observe a distinct gas invasion pattern, where gas progresses through the pore space in the form of disconnected clusters mediated by double and multiple displacement events. Gas advances in a process we name three-phase Haines jumps, during which gas re-arranges its configuration in the pore space, retracting from some regions to enable the rapid fill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(26 citation statements)
references
References 85 publications
0
26
0
Order By: Relevance
“…Instead, by combining pore‐scale imaging with steady‐state three‐phase flow, it has been discovered that gas, in fact, flows in disconnected clusters when injected simultaneously with oil and water in a water‐wet system. Disconnected unsteady‐state gas flow has been previously observed in a strongly oil‐wet three‐phase system, where gas was intermediate‐wet, using synchrotron X‐ray source (Alhosani, Scanziani, Lin, Selem, et al., 2020), but not over a range of fractional flows in steady‐state in a water‐wet system.…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…Instead, by combining pore‐scale imaging with steady‐state three‐phase flow, it has been discovered that gas, in fact, flows in disconnected clusters when injected simultaneously with oil and water in a water‐wet system. Disconnected unsteady‐state gas flow has been previously observed in a strongly oil‐wet three‐phase system, where gas was intermediate‐wet, using synchrotron X‐ray source (Alhosani, Scanziani, Lin, Selem, et al., 2020), but not over a range of fractional flows in steady‐state in a water‐wet system.…”
Section: Resultsmentioning
confidence: 87%
“…Oil and gas are immiscible at the selected experimental conditions. Water has a dynamic viscosity of μ w = 1.40 mPa·s with an interfacial tension of σ ow = 52.1 mNm1 $\text{mN}\cdot {\mathrm{m}}^{-1}$ with oil, and σ gw = 63.7 mNm1 $\text{mN}\cdot {\mathrm{m}}^{-1}$ with gas (Alhosani, Scanziani, Lin, Selem, et al., 2020; Jianhua, 1993; NIST, 2019).…”
Section: Methodsmentioning
confidence: 99%
“…When gas is injected at immiscible conditions, it progresses through the pore space in disconnected clusters by gas-oil-water double and multiple displacements, combined with gas-water direct displacement. This was first observed by Alhosani et al (2020b), who used time-resolved synchrotron imaging to capture the connectivity of gas during gas injection in a strongly oil-wet reservoir rock at immiscible conditions. Figure 10 shows the connectivity of the gas phase during gas invasion at different time-steps-each colour represents a different gas cluster.…”
Section: Immiscible Conditionsmentioning
confidence: 92%
“…In a recent study (Alhosani et al 2021) the authors successfully altered the wettability of a reservoir rock towards strongly oil-wet conditions and visualized, using pore-scale imaging, the hypothesized wettability order. To further confirm the wetting order in the system, the authors quantified the in situ fluid-fluid contact angles (see Table 2), which demonstrated that oil is wetting to both water and gas, gas is non-wetting to oil and wetting to water, while water is non-wetting to both oil and gas (Alhosani et al 2021): this was the case for both the geometric and thermodynamic estimates of contact angles (Alhosani et al 2020b). Moreover, the pore occupancy statistics indicated that, on average, oil resides in the smallest pores and water the biggest, while gas occupies intermediate-sized pores (see Fig.…”
Section: Immiscible Conditionsmentioning
confidence: 99%
See 1 more Smart Citation